2009
DOI: 10.1108/09556220910959990
|View full text |Cite
|
Sign up to set email alerts
|

Selection of ERP suppliers using AHP tools in the clothing industry

Abstract: PurposeThe purpose of this paper is to explore selection of the best ERP suppliers in the clothing industry by using analytic hierarchy process (AHP).Design/methodology/approachAHP is used in order to achieve the paper's purpose; selection criteria are determined by managers and experts.FindingsThree different enterprise resource planning (ERP) suppliers are investigated and best alternative is selected by using AHP. After the best alternative is selected, cost benefit analysis is calculated in order to define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 32 publications
(29 reference statements)
0
12
0
3
Order By: Relevance
“…The review of the state of the art on ERP selection Methods revealed the following methods: AHP (Analytic Hierarchy Process) [1], [13], [16], [17], [23], ANP (Analytic Network Process) [5], [14], [15], [23], PROMETHEE [2], [5], SHERPA (Systematic Help ERP Acquisition), FL (Fuzzy Logic) [3], [12], [15], [17], [18], PM (Priority Matrix), TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) [24], [25], SMART [4].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The review of the state of the art on ERP selection Methods revealed the following methods: AHP (Analytic Hierarchy Process) [1], [13], [16], [17], [23], ANP (Analytic Network Process) [5], [14], [15], [23], PROMETHEE [2], [5], SHERPA (Systematic Help ERP Acquisition), FL (Fuzzy Logic) [3], [12], [15], [17], [18], PM (Priority Matrix), TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) [24], [25], SMART [4].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The hierarchy consisted of: factors, attributes, evaluation items and means. Another AHP model was applied to selecting an ERP system specific to clothing industry suppliers [31]. Criteria were selected based upon discussion with three such suppliers, as well as literature reviews.…”
Section: Modeling Erp Selectionmentioning
confidence: 99%
“…[11], [12]. Ünal and Güner proposed a methodology based on AHP for ERP provider selection for an organization in the textile industry [13]. In the same sector, Cebeci presented another ERP supplier selection methodology based on fuzzy AHP [14].…”
Section: Ahp Methodsmentioning
confidence: 99%